De novo use of generic tacrolimus in liver transplantation – a single center experience with one‐yr follow‐up. (24th October 2014) - Dannhorn, E.; Cheung, M.; Rodrigues, S.; Cooper, H.; Thorburn, D.; Patch, D.; Burroughs, A.K.; O'Beirne, J.
Abstract Use of generic tacrolimus in liver transplantation (LT) could result in cost savings. Generic tacrolimus has been shown to be bioequivalent to innovator tacrolimus in healthy volunteers and renal transplant patients. There are limited data on the de novo use of generic tacrolimus in LT. This study aimed to determine whether the de novo use of generic tacrolimus (Adoport, Sandoz, UK) was associated with differences in outcomes, safety, and cost compared with innovator tacrolimus (Prograf, Astellas, Japan). Methods Patients were studied before and after a programmatic change from de novo IS with Prograf to Adoport. Outcomes, tacrolimus levels, doses, and costs were compared for the first‐yr post‐LT. Results Ninety‐four patients were studied, 46 Prograf, 48 Adoport. No significant differences in rejection, cytomegalovirus infection, acute kidney injury, sepsis, or graft loss were observed between groups. Tacrolimus costs were significantly reduced with the de novo use of Adoport. Day 14 dose normalized levels in Adoport patients showed significant variation but at the day 30 and one yr, there were no significant differences in the doses or levels of tacrolimus between groups. Conclusions Adoport is safe and effective compared to Prograf when used de novo in LT patients. Tacrolimus costs were significantly reduced by the use of Adoport.